Tiller Contributions to Low-Density Corn Biomass and Yield - R. Veenstra; C. Messina; L. Haag; P. V. Vara Prasad; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2020)
Tillers (commonly termed “suckers”) have lower overall yield contributions in corn (Zea maysL.) than in other Poaceae species. Current research evaluating the value of tillers in corn is scarce, particularly under water-limited conditions. This study aims to quantify relationships between tiller, main plant, and full (considering both tiller and main plant fractions) plant aboveground biomass and yields of corn under low plant density scenarios. Experiments were conducted in the 2019 growing season at three sites across Kansas (Garden City, Goodland, and Manhattan) evaluating two tiller-prone corn hybrids common in this region (P0805AM and P0657AM) at two plant densities (10,000 and 17,000 plants/a) with tiller maintenance (YT) or tiller removal (NT) at the V10 growth stage (tenth leaf). Treatments were set in a split-split-plot under a randomized complete block design (RCBD) with three replications. Results showed that full shoot dry biomass at maturity was neutrally or positively influenced by both tiller presence and an increase in plant density. Although yield from ears on the main plant (herein termed as “main plant yields”) can be negatively impacted by tillers, full yield of all portions of the plant (herein “full plant yields”) were neutrally or positively influenced by tiller contributions. Tiller yield variation in this study was influenced by tiller reproductive development, specifically tassel and lateral ear types. Responsible mechanisms and environmental factors influencing these development processes remain largely unknown, and this will be the focus of continuing studies.
Keywords: corn; tiller; plant density; yield; biomass